Pemanfaatan SeemeCV dalam Meningkatkan Kualitas Resume untuk Pencari Kerja - Armandito, Armandito; R Dani, Bima; Gustinar; Arniwita (ORAHUA : Jurnal Pengabdian Kepada Masyarakat, 2025)
Seeme CV is an innovative platform that provides resume creation services with modern and professional designs. This article discusses the implementation of Seeme CV as a community service tool to help job seekers, especially students and new graduates, improve the quality of their resumes. This community service program is carried out through direct training involving the use of Seeme CV features, effective resume content preparation, and personal branding strategies. The results show that participants are able to produce resumes that are more attractive and in accordance with industry needs. This article also discusses the challenges faced during the training and provides recommendations for similar programs in the future. Thus, this program makes a real contribution to preparing a more competitive workforce in the digital era.